Goal Setting in Medical Rehabilitation: A Narrative Review - Thorsten Meyer; Cornelia Weiss2; Farooq Azam Rathore (Journal of the Pakistan Medical Association, 2023)
Goal setting is an integral part of rehabilitation and the rehabilitation process. The aim of rehabilitation is to optimize functioning. Therefore, rehabilitation professionals and patients together have to determine mutually which aspects of functioning they should aim at. From a clinical view, a formal procedure for setting goals should help to motivate patients, ensure cooperation of rehabilitation team members, help to identify relevant blind spots and provide a system to monitor patient changes. Applying goal setting in rehabilitation represents a purpose in its own right, as it serves to strengthen the autonomy of patients and is a valuable tool to integrate personal motives, attitudes, meanings into the rehabilitation process. There is evidence that the introduction of goal setting into rehabilitation practice could enhance health-related quality of life and emotional states, especially self-efficacy. Mixed results have been reported regarding the patient motivation as well as activities and participation outcomes. Keywords: rehabilitation, patient care planning, care goals, patient-centred care, personal autonomy, shared decisionmaking, multidisciplinary care teams